The Sage handbook of qualitative data collection - Flick, Uwe, 1956- (London : SAGE Publications Ltd, 2018)
How we understand and define qualitative data is changing, with implications not only for the techniques of data analysis, but also how data are collected. New devices, technologies and online spaces open up new ways for researchers to approach and collect images, moving images, text and talk. The SAGE Handbook of Qualitative Data Collection systematically explores the approaches, techniques, debates and new frontiers for creating, collecting and producing qualitative data. Bringing together contributions from internationally leading scholars in the field, the handbook offers a state-of-the-art look at key themes across six thematic parts: Part I Charting the Routes Part II Concepts, Contexts, Basics Part III Types of Data and How to Collect Them Part IV Digital and Internet Data Part V Triangulation and Mixed Methods Part VI Collecting Data in Specific Populations.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Qualitative research -- Methodology -- Handbooks, manuals, etc